2012
DOI: 10.1161/circresaha.112.265959
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac P2X 4 Receptors

Abstract: Purinergic receptors have attracted growing interest as therapeutic targets. This perspective focuses on P2X 4 receptors as a new cardioprotective target in heart failure.P urinergic 1 receptors were initially conceived to describe the likely existence of membrane receptors responding to adenosine triphosphate (ATP) (P2 receptors) or its breakdown product adenosine (P1 receptors) in causing nonadrenergic, noncholinergic relaxation of gut smooth muscle. 1 Cloning of these receptors has yielded insights into the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…Possible candidates include cyclic GMP and protein kinase G or cellular protein nitrosylation. 5,30 Our study also has implications for the development of P2X4R antagonist as a new therapy to treat pain. 31 Because the endogenous cardiac myocyte P2X4R is cardioprotective, its antagonism during pain control may be deleterious to those individuals under cardiac stress, including HF.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…Possible candidates include cyclic GMP and protein kinase G or cellular protein nitrosylation. 5,30 Our study also has implications for the development of P2X4R antagonist as a new therapy to treat pain. 31 Because the endogenous cardiac myocyte P2X4R is cardioprotective, its antagonism during pain control may be deleterious to those individuals under cardiac stress, including HF.…”
Section: Discussionmentioning
confidence: 83%
“…For immunoprecipitation, we used mouse monoclonal eNOS (BD Bioscience; 1–3 μg) and rabbit polyclonal P2X4 (Alomone; 2 μg). L-N 5 -(1-iminoethyl) ornithine hydrochloride (L-NIO; Sigma-Aldrich) was administered via intraperitonel route at 40 mg/kg per day 20 beginning at 3 days before coronary ligation or TAC until cardiac function determinations at 7 days postsurgery.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Transgenic overexpression of P2X4R in mouse heart led to enhanced cardiac contractile performance after ischaemic infarction and increased survival at 1 and 2 months after infarction; this suggested that enhanced contractile function via P2X4R of the non-infarcted areas was likely to be a rescuing mechanism [606]. A recent review discusses P2X4R as targets for cardiac ischaemia [607].…”
Section: Ischaemiamentioning
confidence: 99%